PENERAPAN PRINSIP-PRINSIP PERJANJIAN ISLAM DALAM PEMBUATAN AKTA NOTARIIL - SYAFWATUN NIDA (PREMISE LAW JURNAL, 2015)
Akad in the Islamic law is a contact made by the partiesconcerned (aqaid) based on the agreement (ikhtiari) which is indicated by presence of ijab and qobul on the aqad object which must be absent from the prohibition stipulated in the legal provision in the Islamic contract. The research used judicial normative and descriptive analytic. The principle of amanah/ keeping the promisewhich is line with the principle of pacta sunt sevanda, the principle of taswiyah (equality) which is in line with the principle of equality in the contract law in the Civil Code. A Notary should understand thoroughly the defference and the similarity of the principles of akad in the Islamic legal contract and in the legal contract found in the Civil code. In consequence, the implementation of making a notarial authentic deed must be based on the guidance of akad in the Islamic law. The principle of the akad must be in line with the procedure of making a notarial authentic deed, base on the legal principles of a contract in the Civil Code according to the prevailing regulations in making a notarial authentic deed. Keywords : Priciples of Agreement, Islamic Law, Notarial Deed